EFEKTIVITAS PENGGUNAAN NEARPOD TERHADAP HASIL BELAJAR SISWA - Azzahra, Fauziah; Azizah, Wahyu Sukma Nur; Viratama, Ika Putra (Sindoro: Cendikia Pendidikan, 2024)
The need for interesting and interactive learning media is increasing in the digital era. Nearpod is a digital learning platform that offers various interactive features, such as videos, images, quizzes and assessments to increase student engagement and learning outcomes. This research aims to determine the effectiveness of using Nearpod on student learning outcomes and interest in learning.